1995
DOI: 10.1111/j.1476-5381.1995.tb16360.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effects of two new arginine/citrulline analogues on constitutive and inducible nitric oxide synthases in rat aorta

Abstract: 1 New potent inhibitors of nitric oxide synthase (NOS) may be useful in the treatment of septic shock, a disorder characterized by a vascular hyporeactivity to catecholamines caused by an overproduction of nitric oxide (NO-). We examined the effects of L-thiocitrulline (L-TC) and S-methyl-L-thiocitrulline (L-SMTC), novel NOS inhibitors, on the constitutive and inducible NOS in rat aorta and compared those effects with inhibition due to NG-methyl-L-arginine (L-NMA). 2 Phenylephrine evoked similar concentration-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Among arginine derivatives, N ω -allyl-L-arginine and N ω -propyl-L-arginine appear to affect catalytic activity with a mechanism more complex than simple competitive inhibition and display relative selectivity towards different isoforms by inhibiting some of them at concentrations much lower than others [466,467,468]. Other amino acid analogs are effective NOS inhibitors, sometimes showing some degree of selectivity, as it is the case for S-methyl and Sethyl derivatives of L-thiocitrulline whose action is exerted through block of the heme-dependent oxygen activation [469,470]. Derivatives of other amino acids, such as N 5 -(1-iminoethyl)-L-ornithine (L-NIO) and N 6 -(1-iminoethyl)-Llysine (L-NIL) are effective NOS inhibitors showing a limited degree of selectivity [460].…”
Section: Nitric Oxide Synthase Inhibitorsmentioning
confidence: 95%
“…Among arginine derivatives, N ω -allyl-L-arginine and N ω -propyl-L-arginine appear to affect catalytic activity with a mechanism more complex than simple competitive inhibition and display relative selectivity towards different isoforms by inhibiting some of them at concentrations much lower than others [466,467,468]. Other amino acid analogs are effective NOS inhibitors, sometimes showing some degree of selectivity, as it is the case for S-methyl and Sethyl derivatives of L-thiocitrulline whose action is exerted through block of the heme-dependent oxygen activation [469,470]. Derivatives of other amino acids, such as N 5 -(1-iminoethyl)-L-ornithine (L-NIO) and N 6 -(1-iminoethyl)-Llysine (L-NIL) are effective NOS inhibitors showing a limited degree of selectivity [460].…”
Section: Nitric Oxide Synthase Inhibitorsmentioning
confidence: 95%
“…Unfortunately, Wang and colleagues (2009) did not use an inhibitor that specifically targets eNOS, thus limiting the specificity of their findings. Another nNOS inhibitor (SMTC) has been reported to be a very potent vasopressor in anesthetized rats (Narayanan et al, 1995) and an inhibitor of endothelium‐dependent relaxation responses of the isolated rat aorta, with a potency similar to that of a broad spectrum NOS inhibitor (Joly et al, 1995). These data strongly suggest that SMTC causes significant eNOS inhibition in vivo and, consequently, its use to study the function of nNOS‐derived NO in intact animals is not advised (Moore and Handy, 1997).…”
Section: Creating a Permissive Scenario For Axonal Regenerationmentioning
confidence: 99%
“…One approach has been to develop novel substrate analogues of L-arginine. Compounds such as aminoguanidine (Griffiths et al, 1994), isothioureas (Southan et al, 1995) and L-thiocitrulline (Joly et al, 1995), have been reported to exhibit some isoform selectivity for iNOS. However, compounds based on inhibiting enzyme expression might also show some selectivity and we reported that anti-fungal imidazoles inhibit expression of the iNOS activity in murine macrophages (Bogle et al, 1994).…”
Section: Introductionmentioning
confidence: 99%